A BIOMECHANICAL STUDY OF YOUTH TABLE TENNIS PLAYERS FOR ENHANCING PERFORMANCE AND PREVENTING INJURY - Kholmatov Bekzod Uralovich (Bright Mind Publishing, 2025)
Present article explains a biokinematic analysis of young table tennis players to quantify movement patterns during key strokes and footwork. By identifying biomechanical inefficiencies linked to both performance limitations and common overuse injuries, the research provides a data-driven framework for optimizing technique and implementing targeted injury prevention strategies in youth training
Keywords: Biokinematics, table tennis, youth sports, performance optimization, injury prevention.